2020
DOI: 10.1136/bmjopen-2019-033085
|View full text |Cite
|
Sign up to set email alerts
|

Association between GP participation in a primary care group and monitoring of biomedical and lifestyle target indicators in people with type 2 diabetes: a cohort study (ELZHA cohort-1)

Abstract: ObjectiveWhether care group participation by general practitioners improves delivery of diabetes care is unknown. Using ‘monitoring of biomedical and lifestyle target indicators as recommended by professional guidelines’ as an operationalisation for quality of care, we explored whether (1) in new practices monitoring as recommended improved a year after initial care group participation (aim 1); (2) new practices and experienced practices differed regarding monitoring (aim 2).DesignObservational, real-life coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The aims of this approach include improving oversight of the diabetes population and up-to-date monitoring outcomes as well as tailored support for practices to achieve optimal delivery of care. 20 Comparable approaches resulted in the impressive amelioration of care delivery, regardless of socioeconomic deprivation. 28,29 Interestingly, the crude findings-suggesting significantly lower monitoring in deprived neighbourhoods and better monitoring in advantageous neighbourhoods-are in line with previous findings in other settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aims of this approach include improving oversight of the diabetes population and up-to-date monitoring outcomes as well as tailored support for practices to achieve optimal delivery of care. 20 Comparable approaches resulted in the impressive amelioration of care delivery, regardless of socioeconomic deprivation. 28,29 Interestingly, the crude findings-suggesting significantly lower monitoring in deprived neighbourhoods and better monitoring in advantageous neighbourhoods-are in line with previous findings in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that care group participation by GPs is associated with an improvement of the monitoring of biomedical and lifestyle-related target indicators in people with type 2 diabetes. 20 Monitoring is considered an important measure for quality of care, since it is associated with better HbA1c levels. 21 Studies on health inequalities in primary and secondary diabetes care have shown that a lower socioeconomic status is associated with worse monitoring and outcomes in people with diabetes, including early death.…”
Section: Socioeconomic Status and Barriers In Diabetes Carementioning
confidence: 99%
See 2 more Smart Citations
“…Structured type 2 diabetes primary care is associated with improved monitoring of key biomedical and lifestyle-related health indicators [ 10 , 11 ] and better monitoring of these indicators is associated with lower HbA1c levels [ 12 ], particularly in poorly-controlled people [ 13 ]. However, given that guideline compliance is known to be affected by physician attitudes [ 14 ], protocol-based delivery of diabetes primary care is the subject of growing discussion.…”
Section: Introductionmentioning
confidence: 99%